A Study of Relations between Optimal Network Card Mode and Data Transmission Size (Journal of Informatics and Mathematical Sciences, 2017)
There is a necessity to study the relations between optimal network card mode and its data transmission size, in order to investigate if a specific network card mode is more suitable for a certain size of transmission. Three network card modes are examined, which are active wait, passive wait, and watermark. The existing data of 47 different transmission sizes and their respective optimal network card modes are observed. The analyses conclude that all network card modes are suitable for all levels of transmission size (small, medium, and big), as long as their optimal value takes place. However, it is better to implement the network card mode with the least generated kernel interrupts. Hence, the CPU cycles can be preserved.
Keywords: Network card mode; Active wait; Passive wait; Watermark; Transmission size; Nurika equation